Uporaba endoskopskega ultrazvoka pri bolnikih z dispepsijo - Godec Novak, Manca (Zdravniški vestnik, 2006)
Background. Dyspepsia is a common symptom occuring in 25-40 % of the general population. Treatment of dyspeptic patients is a diagnostic and therapeutic challenge. Endoscopic ultrasound is one of diagnostic methods when treating dyspeptic patients. The purpose of this retrospective analysis was to evaluate the usefulness of endosonography in patients with dyspeptic complaints. Patients and methods. Between June 2003 and May 2005 we performed endoscopic ultrasound in 133 patients. Despite accurate anamnesis, clinical examination, laboratory tests, abdominal ultrasound and upper endoscopy the cause of upper abdominal pain in these patients during the diagnostic procedures could not be established. Results. Pathology in the common bile duct, papilla of Vater, gallblader and pancreas were verified in 93 patients (70 %). The most common diagnosis was choledocholithiasis, in 40 % of patients, followed by cholecystolithiasis, in 13 % of patients. Enlarged papilla of Vater with a normal common bile duct was noticed in 12 % of patients and a widened common bile duct with a diameter larger than 7 mm without any signs of gallstones was found in 3 % of patients. In two patients (1 %) we found a tumour formation in front of papilla of Vater growing outwardly from the bile duct wall. Also in two patients (1 %) we noticed just enlarged lymph nodes in the surroundings without any other pathology. In three patients (1.5 %) we noticed chronic changes of the pancreas that were not described with the previously performed ultrasound. Conclusions. Endoscopic ultrasound proved to be an excellent supplementary diagnostic method for patients with dyspepsia when other tests and examinations do not explain the cause of complaints. The use of this imaging method enables more selective use of invasive and risky examinations.
Keywords: Cholelithiasis; Common Bile Duct; diagnosis; Diagnostika; Dispepsija; Dyspepsia; endoscopy; endoskopija; Endosonografija; Endosonography; Skupni žolčni vod; ultrazvočna diagnostika; Žolčni kamni